2022
DOI: 10.3390/machines10100888
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sensor Integration on the Load Carrying Capacity of Gears

Abstract: Classical machine elements have been around for centuries, even millennia. However, the current advancement in Structural Health Monitoring (SHM), together with Condition Monitoring (CM), requires that machine elements should be upgraded from a not-simple object to an intelligent object, able to provide information about its working conditions to its surroundings, especially its health. However, the integration of electronics in a mechanical component may lead to a reduction in its load capacity since the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The authors have identified the following examples that can be categorized as sensor-integrating gears: i) Additively manufactured metal spur gear wheel with an integrated accelerometer; [115] ii) case-hardened metal helical gear wheel with hall sensor, accelerometer, temperature sensor, and microphone inside; [116] iii) plastic spur gear wheel with an eddy-current sensor in the teeth; [117] iv) metal spur gear wheel with resistance sensors on the side; [118] v) sensor-integrating metal spur gear with accelerometer on the side. [119,120]…”
Section: Characteristic Parameters On Sensor-integrating Gearsmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors have identified the following examples that can be categorized as sensor-integrating gears: i) Additively manufactured metal spur gear wheel with an integrated accelerometer; [115] ii) case-hardened metal helical gear wheel with hall sensor, accelerometer, temperature sensor, and microphone inside; [116] iii) plastic spur gear wheel with an eddy-current sensor in the teeth; [117] iv) metal spur gear wheel with resistance sensors on the side; [118] v) sensor-integrating metal spur gear with accelerometer on the side. [119,120]…”
Section: Characteristic Parameters On Sensor-integrating Gearsmentioning
confidence: 99%
“…There are solutions that are not comparable, because not every publication lists all the necessary properties and the parameters of the gears. Most information is given in the publication by Bonaiti et al [116] where the influence of the cavities and possible designs for integration are discussed in detail. The gear is casehardened.…”
Section: Load-carrying Capacity Of Sensor-integrating Gearsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, attention has shifted from ordinary machine elements to sensor-integrated machine elements [4,5]. Examples of the first approaches of sensor-integrated machine element are a sensor-integrated gear, published by Bonaiti et al [6] and prototypes of smart couplings proposed by Schork et al [7]. Kirchner et al presented an extensive overview of various machine elements with integrated sensors from bolts, couplings and bearings to gears and gear shafts [8].…”
Section: Introductionmentioning
confidence: 99%